A Survey on Perception of Youth Towards Entrepreneurship in Ambernath - Kedare, Shubhangi M. (SFIMAR Research Review, 2017)
Entrepreneurship is need of the hour today. Since, government jobs are tough to get ina country such as India, entrepreneurs and entrepreneurship should be heartily welcomed. This is all the more important considering the fact that the country's young population is more than 65%; signitying abundant manpower. Entrepreneurship not only helps in developing economic activities by creating employment opportunities, it also improvises the standard of living in the society. This paper is an attempt to find out the perception of youth towards entrepreneurship, the ways and means through which entrepreneurial qualities can be inculcated among youth as well. It is also an effort to find out the whether today's youth is ready and willing to take up entrepreneurship as their career. Through this research it is also found that there is a dire need for training and other facilities for the young population to take up entrepreneurship as their career.